ABC News Poll, July 1991 ([Verlag nicht ermittelbar], 1992)
This data collection is part of a continuing series of monthly surveys that evaluate the Bush presidency and solicit opinions on a variety of political and social issues. Topics covered include the economy, foreign affairs, the situation in the Persian Gulf, and the recession. In addition, respondents were questioned in depth regarding health care and health insurance. They were asked about the quality of health care, health insurance coverage, the health insurance system in the United States, whether they would choose an inexpensive health care program that did not allow them to choose their own doctors or an expensive one that permitted that choice, and whether they would prefer private health insurance or national health insurance. Respondents were also asked if they thought the Persian Gulf War was worth fighting, if the United States should bomb Iraq if the United States government believed Iraq was secretly trying to make nuclear weapons, if they approved of Clarence Thomas's nomination to the Supreme Court, and if they had favorable impressions of certain persons, organizations, and countries. Among the other subjects addressed are the economic and political system changes of the Soviet Union, cutting the number of long-range nuclear missiles, the Middle East peace conference, the United States House of Representatives election in November, and AIDS testing. Background information on respondents includes political alignment, 1988 presidential vote choice, education, age, religion, social class, marital status, number of people in household, labor union membership, employment status, race, income, sex, and state/region of residence.